2018
DOI: 10.4143/crt.2017.283
|View full text |Cite
|
Sign up to set email alerts
|

NUDT15 Variants Cause Hematopoietic Toxicity with Low 6-TGN Levels in Children with Acute Lymphoblastic Leukemia

Abstract: Purpose We aimed to identify the impact of NUDT15 variants on thiopurine intolerance and 6-thioguanine nucleotide (6-TGN) levels in Korean children with acute lymphoblastic leukemia (ALL).Materials and Methods Genotyping of NUDT15 was tested in 258 patients with ALL registered at Samsung Medical Center. Patients were classified into normal-activity (wild-type), intermediate-activity (heterozygous variant), and low-activity groups (homozygous or compound heterozygous variant). Clinical and laboratory features d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 33 publications
(56 reference statements)
6
26
0
Order By: Relevance
“…NUDT15 , another important gene with a similar pathway as TPMT , was first identified as a candidate gene by a genome‐wide association study (GWAS) of inflammatory bowel disease patients and in children with ALL . NUDT15 was associated with thiopurine‐related hematopoietic toxicity and has been confirmed in several other studies to be associated with thiopurine tolerance and/or thiopurine‐related toxicity in leukaemia patients . In this study, two SNPs of NUDT15 (rs116855232 and rs186364861) were identified in association with thiopurine metabolites and therapeutic interruption which confirmed and reflected previous findings on its association with thiopurine‐related hematopoietic toxicity (Tables ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…NUDT15 , another important gene with a similar pathway as TPMT , was first identified as a candidate gene by a genome‐wide association study (GWAS) of inflammatory bowel disease patients and in children with ALL . NUDT15 was associated with thiopurine‐related hematopoietic toxicity and has been confirmed in several other studies to be associated with thiopurine tolerance and/or thiopurine‐related toxicity in leukaemia patients . In this study, two SNPs of NUDT15 (rs116855232 and rs186364861) were identified in association with thiopurine metabolites and therapeutic interruption which confirmed and reflected previous findings on its association with thiopurine‐related hematopoietic toxicity (Tables ).…”
Section: Discussionsupporting
confidence: 90%
“…Clinical information including 6‐MP dosage (mg/body surface area/day), duration of 6‐MP treatment, and adverse effects related to treatment were investigated. The treatment protocol has been described in detail previously . Patients who were over 10 years of age or under 12 months or who had initial white blood cell (WBC) count of 50 × 10 9 L −1 or more were considered as high‐risk ALL patients (the others were standard risk ALL patients) according to the risk stratification criteria of the National Cancer Institute .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of 404 Taiwan Chinese patients with ALL, 5 patients were homozygous (TT) for the NUDT15 variant and the maximal tolerable daily dose of 6-MP in this group was 9.4±3.7 mg/m 2 /day (24). A previous study demonstrated that 5 out of 182 Korean pediatric patients with ALL were homozygous for the NUDT15 variant and the lowest dose of 6-MP administered was 7.5 mg/m 2 /day (25). Previous studies suggest that a comprehensive pharmacogenetic model incorporating the specific genetic variation of NUDT15 may allow for further personalized thiopurine therapy (13,(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 97%
“…A previous study demonstrated that 5 out of 182 Korean pediatric patients with ALL were homozygous for the NUDT15 variant and the lowest dose of 6-MP administered was 7.5 mg/m 2 /day (25). Previous studies suggest that a comprehensive pharmacogenetic model incorporating the specific genetic variation of NUDT15 may allow for further personalized thiopurine therapy (13,(23)(24)(25)(26). Although genetic testing prior to treatment revealed that the patient possessed the TPMT wild-type allele, the patient suffered from severe myelosuppression, in particular, neutropenia and hyperpigmentation, all of which led to a lung infection and treatment delay.…”
Section: Discussionmentioning
confidence: 99%